Fabricação de salame tipo hamburguês com substituição parcial de sódio - Barbosa, Roberta Garcia (2009)
The excessive intake of sodium is related to hypertension and consequently to an increased risk of cardiovascular diseases. The consumption of sodium exceeds the nutritional recommendations in most industrialized countries. Sodium chloride is the main source of sodium in the diet. In developed countries, meat products are one of the major sources of sodium in the form of sodium chloride. This study was aimed at producing a Hamburg-type dry fermented sausage with low sodium levels, but keeping the traditional characteristics appreciated in this product. For this purpose, we evaluated potassium chloride and magnesium chloride as partial substitutes for sodium chloride (45, 50 and 55% substitution on mass basis). The pH, temperature, weight loss, lactic acid bacteria counts, aerobic mesophilic bacteria counts, Salmonella, total and fecal coliforms were assessed during and after the production of dry fermented sausages. At the end of the production the sausages were also submitted to proximate composition, mineral, water activity, objective color and sensory analyses. Results indicate that the replacement of 45 to 55% NaCl with KCl or MgCl2 yields Hamburg-type dry fermented sausages that have physico-chemical and microbiological characteristics suitable for trading. These products were within the Brazilian legal limits for moisture, protein, fat, water activity, coliforms and Salmonella. Among the formulations developed, the highest moisture was found in MgCl2-containing sausages, which also had the lowest contents of ash and chloride. Water activity was lower in the sausages with KCl. Although the replacement of 45% NaCl with KCl or MgCl2 have improved the sensory characteristics of Hamburg-type dry fermented sausage, the replacement of 50% NaCl with KCl and 55% NaCl with MgCl2 also appear to be viable, since they yielded products with sensory acceptability similar to that of control.